Prenatal Exposure to Lead and Chromium is Associated with IL-13 Levels in Umbilical Cord Blood and Severity of Atopic Dermatitis: COCOA Study - Kim, Jihyun; Kim, Seonwoo; Woo, Sook-young; Chung, Jin-Yong; Hong, Young-Seoub; Oh, Se-Young; Choi, Suk-Joo; Oh, Soo-Young; Kim, Kyung Won; Shin, Youn Ho; Won, Hye-Sung; Lee, Kyung-Ju; et al. (Immune network, 2019)
There have been few studies investigating the association between atopic dermatitis (AD) and prenatal exposure to heavy metals. We aimed to evaluate whether prenatal exposure to heavy metals is associated with the development or severity of AD in a birth cohort study. A total of 331 subjects were followed from birth for a median duration of 60.0 months. The presence and severity of AD were evaluated at ages 6 and 12 months, and regularly once a year thereafter. The concentrations of lead, mercury, chromium, and cadmium in umbilical cord blood were measured by inductively coupled plasma mass spectrometry. Cord blood mononuclear cells (CBMCs) were isolated and stimulated for analysis of cytokine production using ELISA. Heavy metal levels in cord blood were not associated with the development of AD until 24 months of age. However, a positive correlation was observed between the duration of AD and lead levels in cord blood (p=0.002). AD severity was also positively associated with chromium concentrations in cord blood (p=0.037), while cord blood levels of lead, mercury, and cadmium were not significantly associated with AD severity (p=0.562, p=0.054, and p=0.055, respectively). Interleukin-13 production in CBMCs was positively related with lead and chromium levels in cord blood (p=0.021 and p=0.015, respectively). Prenatal exposure to lead and chromium is associated with the persistence and severity of AD, and the immune reaction toward a Th2 polarization.